Hierarchical equilibrium in multilevel control system - E M Voronov; A A Karpunin; V A Serov (RUDN Journal of Engineering Research, 2008)
In the article the new concept of hierarchical equilibrium in multilevel control systems for inter-level interaction optimization on the basis of the generalization of Stackelberg's strategy for hierarchical differential games is formulated. The sufficient conditions of control law (strategy) optimality of the level-subsystems of the multi-object multicriteria systems (MMS) are obtained for two-level control system. The approximate iteration procedure of obtaining the hierarchical equilibrium on the basis of the program-corrected control law (strategy) of both MMS-subsystem levels is proposed. The block diagram of the two-level aircraft control and stabilization system is formed, application of obtained procedure in which has the practical value.